Methodologies of life, research and struggle: the Panhῖ experience - Apinaje, Sheila Baxy P. Castro; Apinaje, Júlio Kamêr Ribeiro; Horta, Amanda; Rocha, Welitânia de Oliveira; Morais Neto, Odilon Rodrigues de (Saúde e Sociedade, 2023)
This essay presents the reflections of Sheila Baxy P. Castro Apinaje and Júlio Kamêr Ribeiro Apinaje on their work as researchers of the Platform for Anthropology and Indigenous Responses to covid-19 (PARI-c), in the Apinaje Indigenous Land, in the context of the global health crisis caused by the new coronavirus. Through the description of the research procedures adopted, the authors appropriate the concept of methodology in a particular and creative way, reflecting not only on the strategies to produce academic knowledge, but also on the urge to align these strategies to Panhĩ struggles for the protection of their autonomy over their ways of life and their territory.